Evolutionary impact assessment: accounting for evolutionary consequences of fishing in an ecosystem approach to fisheries management - Laugen, Ane T; Engelhard, Georg H; Whitlock, Rebecca; Arlinghaus, Robert; Dankel, Dorothy J; Dunlop, Erin S; Eikeset, Anne M; Enberg, Katja; Jørgensen, Christian; Matsumura, Shuichi; Nusslé, Sébastien; Urbach, Davnah; et al. (Fish and fisheries (Oxford, England), 2014)
Managing fisheries resources to maintain healthy ecosystems is one of the main goals of the ecosystem approach to fisheries (EAF). While a number of international treaties call for the implementation of EAF, there are still gaps in the underlying methodology. One aspect that has received substantial scientific attention recently is fisheries‐induced evolution (FIE). Increasing evidence indicates that intensive fishing has the potential to exert strong directional selection on life‐history traits, behaviour, physiology, and morphology of exploited fish. Of particular concern is that reversing evolutionary responses to fishing can be much more difficult than reversing demographic or phenotypically plastic responses. Furthermore, like climate change, multiple agents cause FIE, with effects accumulating over time. Consequently, FIE may alter the utility derived from fish stocks, which in turn can modify the monetary value living aquatic resources provide to society. Quantifying and predicting the evolutionary effects of fishing is therefore important for both ecological and economic reasons. An important reason this is not happening is the lack of an appropriate assessment framework. We therefore describe the evolutionary impact assessment (EvoIA) as a structured approach for assessing the evolutionary consequences of fishing and evaluating the predicted evolutionary outcomes of alternative management options. EvoIA can contribute to EAF by clarifying how evolution may alter stock properties and ecological relations, support the precautionary approach to fisheries management by addressing a previously overlooked source of uncertainty and risk, and thus contribute to sustainable fisheries.